FRP-confined tuff masonry columns: regular and irregular stone arrangement. (1st April 2019) - Sandoli, A.; Ferracuti, B.; Calderoni, B.
Abstract: Fiber-Reinforced Polymer (FRP) represents one of the most diffuse and effective strengthening technique for retrofitting columns in existing buildings when presenting insufficient mechanical properties. In fact, the confinement effect provided by wraps with high-tensile strength and stiffness induces significant enhancement of the mechanical behaviour. In this paper experimental results of axial compression tests on both un-confined and FRP-confined prismatic yellow tuff masonry columns are presented. In particular, two types of masonry arrangements, regular and irregular, were reproduced in order to investigate the effectiveness of the confinement on column typologies widely used in the past in Southern Italy and Mediterranean basin. The performed experimental tests allowed to obtain the constitutive axial and transversal stress-strain laws and to evaluate the improvement of the mechanical behaviour, in terms of strength and ductility, due to FRP confinement. The results have highlighted a significant difference in the shape of the constitutive law for confined masonry with respect to the one of confined concrete. Contrary to FRP confined concrete members, in the case of confined masonry members specific theoretical constitutive model has been not yet developed. To this aim, in this paper the various stress-strain laws developed for FRP-confined concrete elements has been applied to masonry elements too and a comparative analyses between experimental and theoretical results has been carried out.